2021
DOI: 10.1111/jerd.12740
|View full text |Cite
|
Sign up to set email alerts
|

Masking ability of bleach‐shade resin composites using the multilayering technique

Abstract: Objective Evaluate the masking ability of bleach‐shade resin composites applied by multilayering techniques over colored substrates. Materials and methods Disc‐shaped specimens were fabricated from bleach‐shade resin composites using different multilayering techniques. Substrates were produced in opaque ceramic discs simulating colored substrates (A2, A3, A3.5, C2, C3, C4) and a bleached tooth (0M1). Color coordinates were obtained using a reflectance spectrophotometer. Color difference was calculated by CIEDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…However, few studies have been conducted on the optical properties of bleach shade composites [ 32 ]. In a recent study, which examined the masking ability of bleach shade composite resins in different layering techniques, it was observed that they cannot mask the different background colors [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have been conducted on the optical properties of bleach shade composites [ 32 ]. In a recent study, which examined the masking ability of bleach shade composite resins in different layering techniques, it was observed that they cannot mask the different background colors [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three brands of 3Y‐TZP zirconia were selected to fabricate 45 anterior crowns with 1 mm labial thickness, using three different manufacturing techniques: (a) monolithic ( n = 5), (b) cut‐back and enamel layering (bi‐layer) ( n = 5), (c) cut‐back and dentine and enamel layering (tri‐layer) ( n = 5). The sample size was based on the results from previous studies 33–37 . The zirconia and the veneering ceramics used in this study are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was based on the results from previous studies. [33][34][35][36][37] The zirconia and the veneering ceramics used in this study are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Although extensive research has been recently conducted on the masking ability of restorative materials [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], there is still missing information on how color differences might impact visual perception when translucent restorations are evaluated over different discolored substrates. Furthermore, there is little information about the colorimetric behavior of monolithic and layered zirconia crowns in combination with various abutment colors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is little information about the colorimetric behavior of monolithic and layered zirconia crowns in combination with various abutment colors. Most studies evaluated the masking ability using rectangular or disc samples [ 12 , 13 , 15 , 16 , 17 , 19 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], which do not reproduce the clinical conditions met in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%